Yoga wellness tourism: a study of marketing strategies in India. Issue 6 (9th September 2019) - Telej, Ewelina; Gamble, Jordan Robert
Abstract : Purpose: The purpose of this paper is to examine marketing strategies that India is currently applying to promote itself as a competitive yoga destination. Design/methodology/approach: The methodological approach consisted of a constructivist research paradigm, a qualitative methodology and an interview-based data collection method. Ten in-depth, semi-structured interviews were conducted with yoga practitioners from various backgrounds and yoga levels who have travelled to India for yoga tourism purposes. Findings: The findings determined that interpretation of yoga tourism is crucial in the choice of marketing approach adopted by destinations offering yoga retreats because, as the study has shown, various perceptions of yoga constitute the basis for particular promotional strategies. Research limitations/implications: Future research could expand on the sample size and demographics of the current study by investigating, possibly through comparative means, larger groups of more diversified yoga practitioners from different countries or backgrounds. Practical implications: It was recommended that India's tourism marketers re-design their approach concerning an 'authentic' yoga experience. Indian destination marketing organisations should target those searching for an authentic yoga experience and use imagery that is realistic. Originality/value: The findings of this study have led to the re-positioning of yoga tourism in India, utilising a unique combinative approach in which a more inclusive concept of wellness is juxtaposed against a lack of any religious referencing. It was also revealed that the motivations of yoga tourists are only partially targeted through an undifferentiated strategic marketing approach.